2016
DOI: 10.1038/sj.bdj.2016.297
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of children undergoing dental extractions under general anaesthesia in Wolverhampton: 2007-2012

Abstract: A clear dental public health issue has been reinforced through the relatively high level of DGA activity reported. Though rigorous caries prevention remains the ultimate goal, a better assessment and discharge process may help reduce the need for first time DGAs as well as repeats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…106 There are also numerous studies stating that, on average, children aged 5-9 years were more likely to be admitted for DGAs. 41,49,62,69,98,99,[107][108][109][110][111][112][113][114][115] Children aged 5-9 may experience more DGAs due to their primary teeth being less resistant to caries, and their age making treatment under local anaesthetic less likely when compared to older children (10-14 years), where permanent teeth are present. 116 Most studies, with rare exceptions, 113 have found males to be more likely to undergo a DGA.…”
Section: ) Socio-demographic and Geographical Characteristics Of Children Undergoing Dgas A) Agementioning
confidence: 99%
See 1 more Smart Citation
“…106 There are also numerous studies stating that, on average, children aged 5-9 years were more likely to be admitted for DGAs. 41,49,62,69,98,99,[107][108][109][110][111][112][113][114][115] Children aged 5-9 may experience more DGAs due to their primary teeth being less resistant to caries, and their age making treatment under local anaesthetic less likely when compared to older children (10-14 years), where permanent teeth are present. 116 Most studies, with rare exceptions, 113 have found males to be more likely to undergo a DGA.…”
Section: ) Socio-demographic and Geographical Characteristics Of Children Undergoing Dgas A) Agementioning
confidence: 99%
“…142,143 Similarly, across several countries it has been shown that minority groups can also experience higher numbers of extracted teeth. 114 The remoteness of some Aboriginal and indigenous groups also presents a significant barrier to access, as does the socioeconomic status of these groups. 101,132 Similar patterns have been found for those with migrant backgrounds in European based studies, 123,144,145 despite some research finding little difference according to ethnicity regarding the ability to complete treatment without a DGA 55 or in the number of decayed teeth extracted.…”
Section: C) Ethnicity and Culturementioning
confidence: 99%
“…Tooth extraction under DGA is now the leading cause of hospital admission for children aged 5–9 years old, 8 with trends for increasing admissions and younger age at admission. 9 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…A recent study exploring the characteristics of children who underwent extractions under GA in Wolverhampton showed that children of Mixed ethnicity (defined as neither White nor South Asian in that study) required more extractions than other ethnic groups. 15 However, this may simply be a reflection of ethnic differences in the prevalence and severity of dental caries 24 rather than the preference of clinicians to offer one technique over another for the provision of complex dental care.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies to date have described the characteristics of child patients receiving dental treatment under either CS [9][10][11] or GA. [12][13][14][15][16] A few studies have compared the profile of child patients in the two groups. A study of 76 9-to-15-year-olds referred for GA extractions showed no differences between CS (n=26) and GA groups (n=50) in terms of sex, age or pre-treatment dental anxiety scale scores.…”
Section: Introductionmentioning
confidence: 99%